Assessment Site Attraction in Gunung Mas Agrotourism, Bogor Regency, West Java - Fitriani, Sarah Putri; Manessa, Masita Dwi Mandini; Tambunan, Mangapul Parlindungan; Tambunan, Rudy Parluhutan (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2024)
Gunung Mas Agrotourism is a sub-unit managed by PT Perkebunan Nusantara VIII (PTPN VIII) under the management of Agrotourism and is the largest contributor to PTPN VIII's revenue, which is 70% and most of it comes from the tourism sector. The facilities and activities offered by Gunung Mas Agrotourism also vary, from lodging, restaurants, tourist attractions, and supporting facilities to meet the tourists' needs. To find out the magnitude of tourist interest in tourist attractions, an analysis of the attractiveness of tourist attractions is needed. This study aims to assess tourist attractions based on tourist preferences as well as the availability and accessibility of facilities in the Gunung Mas Agrotourism area, Bogor Regency. The method used is a survey method with a quantitative approach with the Analytical Hierarchy Process (AHP). The results of this study show that horseback riding got the highest meanwhile ATV got the lowest value of attractiveness. It indicates that the easier accessibility as well as the higher number of facilities to a tourist attraction, the greater the value of attractiveness.